2011
DOI: 10.1097/fbp.0b013e32834afef9
|View full text |Cite
|
Sign up to set email alerts
|

Gypenosides improve cognitive impairment induced by chronic cerebral hypoperfusion in rats by suppressing oxidative stress and astrocytic activation

Abstract: Gypenosides (GP), the saponin extract derived from the Gynostemma pentaphyllum Makino, a widely reputed medicinal plant in China, has been reported to have some neuroprotective effects. We used a rat model of chronic cerebral hypoperfusion to investigate the protective effects of GP on the cortex and hippocampal CA1 region and the underlying mechanisms for its inhibition of cognitive decline. Daily doses of 100 and 200 mg/kg GP were orally administered to adult male Sprague-Dawley rats for 61 days after induci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 0 publications
3
40
0
1
Order By: Relevance
“…However, a previous study reported that chronic cerebral hypoperfusion causes learning impairments in the water maze without marked histological alterations in the hippocampus and striatum (Cechetti et al, 2010;Murakami et al, 2005). Several authors have shown that the long-lasting learning deficits observed in these rats are at least partially attributable to damage to the white matter (Zhang et al, 2011). Cho et al (2006) identified that the main areas affected are corpus callosum, optic tract, and internal capsule in rats with chronic cerebral hypoperfusion.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…However, a previous study reported that chronic cerebral hypoperfusion causes learning impairments in the water maze without marked histological alterations in the hippocampus and striatum (Cechetti et al, 2010;Murakami et al, 2005). Several authors have shown that the long-lasting learning deficits observed in these rats are at least partially attributable to damage to the white matter (Zhang et al, 2011). Cho et al (2006) identified that the main areas affected are corpus callosum, optic tract, and internal capsule in rats with chronic cerebral hypoperfusion.…”
Section: Discussionmentioning
confidence: 91%
“…Recent studies designed a mouse model of chronic cerebral hypoperfusion by placing microcoils bilaterally to the common carotid arteries, where the visual pathway is preserved since blood flow in the common carotid arteries albeit reduced is maintained, but still develops working memory (Shibata et al, 2007) as well as reference memory impairments (Nishio et al, 2010)". In addition, several authors describe damage to white matter in the standard model of two vessels, unlike the modified model (Cho et al, 2006;Farkas et al 2007;Zhang et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Preliminary animal research found that inhibiting astrocytic activation improved cognitive impairment induced by chronic cerebral hypoperfusion [4].…”
Section: Introductionmentioning
confidence: 99%
“…Gypenosides are a series of saponins isolated from Gynostemma pentaphyllum (95). They exhibit strong antioxidative properties manifesting as scavenging free radicals and increasing the levels of SOD in brain tissues.…”
Section: Gypenosidesmentioning
confidence: 99%